Moral reasoning in adaptation to climate change. Issue 3 (4th May 2017) - Adger, W. Neil; Butler, Catherine; Walker-Springett, Kate
ABSTRACT: Moral foundations theory argues that moral reasoning is widely observed and fundamental to the legitimacy of relevant governance and policy interventions. A new analytical framework to examine and test how moral reasoning underpins and legitimizes governance and practice on adaptation to climate change risks is proposed. It develops a typology of eight categories of vulnerability-based and system-based moral reasoning that pertain to the dilemmas around adaptation and examines the prevalence of these moral categories in public discourse about specific adaptation issues. The framework is tested using data on climate change impact, adaptation, and societal responsibility, drawn from 14 focus groups comprising 148 participants across the UK. Participants consistently use moral reasoning to explain their views on climate adaptation; these include both vulnerability-based and system-based framings. These findings explain public responses to adaptation options and governance, and have implications for the direction of adaptation policy, including understanding which types of reasoning support politically legitimate interventions.